The Concept of Religious Experience by Rudolf Otto: A Phenomenological Approach - Farid, Farid (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
This study investigates and analyzes the religious experiences of Rudolf Otto using a phenomenological approach. The main objective of this study is to explore Otto's interpretation of religious experience and his contribution to the field of phenomenology. The research problem focuses on understanding how Otto's concept provides a framework for examining religious experiences that go beyond ordinary or everyday experience. The study uses a literature review, document analysis, and phenomenological analysis of Otto's works, including his important text, Das Heilige (The Idea of the Holy), and his personal documents, such as letters, journals, and notes. The study reveals that Otto's concept of the